PERANCANGAN SISTEM INFORMASI MANAJEMEN LOGISTIK DALAM PENANGGULANGAN BENCANA ALAM GUNUNG MERAPI BERBASIS GIS (GEOGRAPHIC INFORMATION SYSTEM) DI YOGYAKARTA - Dwi Yuli Prasetyo; Ema Utami (Seminar Nasional Informatika (SEMNASIF), 2011)
The eruption of Mount Merapi which has struck the Yogyakarta region terrible, and surrounding areas has left a sad story for our nation. Many people, groups or individuals, who want to contribute in providing assistance. The impact of the difficulty of managing aid can be seen, for example: the distribution of relief goods that are not evenly distributed in terms of numbers between regions (barracks / posts) displacement from one another, the kind of relief goods delivered did not match the type desired by each barracks, and special for fast food, many are then broken and outdated because it is delivered to the barracks at the wrong moment and the inappropriate handling. Needed a solution to minimize the problems that arise in disaster relief logistics process is to use the Logistics Management Information System (SIMLOG) Mount Merapi Natural Disaster-Based GIS. Given this system, problems that arise in the process of logistics in the barracks (posts) evacuation will be truly minimized due to the supply of adequate information, so that the community, both groups and individuals, who spontaneously wants to help to know what needed, both in dimension type, amount, time and place (location / posts) barracks in question. Thus, we will be able to bring the community good will who want to help with the refugee community who really want help as appropriate.